PENINGKATAN PENGETAHUAN SISWA SUPM KOTA TEGAL (JAWA TENGAH) MELALUI PENYEBARAN INFORMASI TENTANG TRANSPORTASI UDANG HIDUP SISTEM KERING MENGGUNAKAN MEDIA FILM BINGKAI BERSUARA - Mei Dwi Erlina; Nendah Kurniasari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
This research aims to know influence of dissemination of picture form, influence of music type attendant of frame film narasi voice, and influence of interaction music type attendant of narasi and dissemination of form draw to improve knowledge of target. Sample determined by purposive to 117 student of SUPM Tegal Central Java with clauses have never followed shrimp transportation technique subject live dry system. This research is quasi exsperimental with factorial device 2x2. Free variable compose from 1) Type music factor attendant of narasi two-level that is populer music and dangdut 2) Factor presentation of picture of comparison of foto frame amount: line picture = 75 : 25% and comparison of photo frames amount : line picture = 25 : 75%. Not free variable are the make-up of knowledge of student. Result of research indicate that 1) Usage of pop music as attendant of narasi in presentation of frame film voice more effective to submit information concerning shrimp transportation live dry system to student of SUPM Tegal; 2) Make-up of knowledge of student of SUPM do not influence by difference of presentation of form draw in frame film displaying voice; 3) frame film voice with comparison of photo picture frames amount : line picture = 75 : 25% and accompanied pop music (MPGF) is treated group of combination which most effective in disseminating innovation of transportation of life shrimp dry system. The respondents of sound film frame of MPGT get the biggest score in increasing knowledge compared to the respondents of treated sound film frame of MPGG, MDGF and MDGG;. 4) Sound film frame can be used to disseminate and enhance of diffusion of innovation on transportation of life shrimp dry system, especially to the SUPM students and the people at large.